AUDIT MANAJEMEN UNTUK MENILAI EFEKTIFITAS FUNGSI SUMBER DAYA MANUSIA (STUDI KASUS PG DJATIROTO) - SETIAWAN, AGUS (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to assess the effectiveness of the implementation of the Human Resources function in the PG Djatiroto and to provide recommendations for the weaknesses that occur in the implementation of the Human Resources function. PG Djatiroto as a state-owned companies is required to be able to work professionally.Therefore, this study tried to provide an assessment as a consideration material in performance improvement by the company in the future.This study is a descriptive study using a case study approach. The data that used in this study are primary data and secondary data, and the data collection techniques are done by field studies and literature study. The data analysis is done descriptively by using the management  audit  approach,  which  is  conducting a preliminary examination, reviewing and testing of management control, detailed examination, t and formulating audit reports.The results showed that the implementation of the Human Resources function at PG Djatiroto has been effective even some weaknesses found. This study has also provided recommendations on the weaknesses found.Keywords: Human Resource Functions, Effectiveness, Management Audit.